Lean six sigma and environmental sustainability: a hospital perspective. Issue 1 (2nd January 2018) - Zhu, Qingyun; Johnson, Sharon; Sarkis, Joseph
ABSTRACT: Organizations have demonstrated increasing interest in both leaning and greening activities. Lean manufacturing practices, with an emphasis on waste elimination, have an affinity with environmentally conscious green practices within organizations. Lean practices have diffused across the supply chain and to the service industry, while interest in the greening of supply chains has grown simultaneously. Linking the greening of supply chains and lean practices within a healthcare environment is relatively underexplored. This paper presents a process framework that defines specific dimensions and synergies between lean and green, to support further exploration of green lean supply chains in healthcare and particularly hospitals. In addition, the application of lean and green to hospitals explicitly brings in the third dimension of social sustainability because it focuses on the healthcare industry. The framework is applied to three cases to exemplify opportunities to green hospital processes. The process framework is also used to generate propositions for additional research in this emergent field.